Analisis Faktor Kunci Pemilihan Wirausaha Pada Wirausaha Unggulan Bank Indonesia Provinsi Sulawesi Utara - Sumampouw, Novena (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The purpose of this research is to determine what factors affect the decision of Bank Indonesia to choose the entrepreneur who is worthy to join the Superior Entrepreneurs of Indonesia Central Bank (WUBI). The type of this research is associative research by using factor analysis as data analysis technique. Based on result of this research, it indicates that there are 3 factors determine Bank Indonesia in choosing the entrepreneurs for WUBI. The first factor is Product Uniqueness, the second determined factor is Product Affirmation and the third factor that determines Bank Indonesia in choosing the entrepreneur on joining WUBI is Facility.Keywords: Competitive Advantage, Facility, Market Segementation, Marketing Strategy of the Product, Product Affirmation, Product Uniqueness and WUBI